TRAMPOLINE ACROBATIC FOR PEOPLE OVER FIFTY YEARS OF AGE, AND THEIR INFLUENCE FOR THE BALANCE (Fiep Bulletin - online, 2012)
Many are the evidences concerning the reduction of motor skills in older people. Since aging is a physiological phenomenon common to all human beings, characterized by a progressive process, individual and influenced by several factors, where the systems responsible for balance are greatly affected, with the coming of the age, causing a decrease in performance the ability to maintain balance. Physical activities bring beneficial effects to prevent the cognitive decline of elderly people, as well as the maintenance of functional capacity, reduction in the number of falls and fractures, allowing the elderly a better quality of life. The objective of this study was to investigate the influence of the practice of Acrobatic Trampoline (TA) on balance in elderly women with more than 50 years old (± 63.1 years). However strength tests were performed for upper and lower limbs, balance test, agility test and flexibility test on 10 elderly practitioners gym at least twice a week. It was found that seniors who participated in the training program showed improvement in TA increased in all periods of training, not only the balance in question, but also in other physical valences, subject to testing
Keywords: Aging; Trampoline Acrobatics and balance